Microbial plankton configuration in the epipelagic realm from the Beagle Channel to the Burdwood Bank, a Marine Protected Area in Sub-Antarctic waters ... : تكوين العوالق الميكروبية في المملكة البحرية من قناة بيجل إلى بنك بوردوود، وهي منطقة بحرية محمية في مياه شبه القارة القطبية الجنوبية ... - Valeria A. Guinder; Andrea Malits; Carola Ferronato; Bernd Krock; John E. Garzón-Cardona; Ana María Martínez (OpenAlex, 2020)
Marine microbial plankton hold high structural and functional diversity, however, high-resolution data are lacking in a large part of the Global Ocean, such as in subpolar areas of the SW Atlantic. The Burdwood Bank (BB) is a submerged plateau (average depth 100 m) that constitutes the westernmost segment of the North Scotia Ridge (54°–55°S; 56°–62°W). The BB hosts rich benthic biodiversity in low chlorophyll waters of the southern Patagonian Shelf, Argentina, declared Namuncurá Marine Protected Area (NMPA) in 2013. So far, the pelagic microorganisms above the bank have not been described. During austral summer 2016, we assessed the microbial plankton (0.2–200 μm cell size) biomass and their taxonomical and functional diversity along a longitudinal transect (54.2–55.3°S, 58–68°W) from the Beagle Channel (BC) to the BB, characterized by contrasting hydrography. Results displayed a marked zonation in the composition and structure of the microbial communities. The biomass of phytoplankton >5 μm was 28 times ... : تحمل العوالق الميكروبية البحرية تنوعًا هيكليًا ووظيفيًا عاليًا، ومع ذلك، هناك نقص في البيانات عالية الدقة في جزء كبير من المحيط العالمي، كما هو الحال في المناطق تحت القطبية في جنوب غرب المحيط الأطلسي. ضفة بوردوود (BB) عبارة عن هضبة مغمورة (متوسط العمق 100 متر) تشكل الجزء الغربي من قمة شمال سكوتيا (54°–55°S ؛ 56°–62°W). يستضيف BB التنوع البيولوجي القاعي الغني في المياه منخفضة الكلوروفيل في الجرف الباتاجوني الجنوبي، الأرجنتين، أعلنت منطقة نامونكورا البحرية المحمية (NMPA) في عام 2013. حتى الآن، لم يتم وصف الكائنات الحية الدقيقة السطحية فوق الضفة. خلال صيف أستراليا 2016، قمنا بتقييم الكتلة الحيوية للعوالق الميكروبية (حجم الخلية 0.2-200 ميكرومتر) وتنوعها التصنيفي والوظيفي على طول مقطع طولي (54.2–55.3درجةجنوبًا، 58–68درجةغربًا) من قناة بيجل (BC) إلى BB، والتي تتميز بالهيدروغرافيا المتناقضة. أظهرت النتائج تقسيمًا ملحوظًا في تكوين وهيكل المجتمعات الميكروبية. كانت الكتلة الحيوية للعوالق النباتية أكبر من 5 ميكرومتر أعلى 28 مرة في كولومبيا البريطانية، ويعزى ذلك أساسًا إلى ازدهار الدياتوم الكبير، مقارنة بالمياه المحيطية ...